Seismic demand on columns in special concentrically braced frames. (1st August 2018) - Momenzadeh, Seyedbabak; Shen, Jay
Highlights: Columns in special concentrically braced frames (SCBFs) experience yielding. Flexural demand on the columns in SCBFs is significant and cannot be neglected. Brace fracturing under design earthquake may result in column fracture. Abstract: A study on the seismic demand on the columns in special concentrically braced frames is presented to address two concerns. First, whether or not the columns remain elastic during an earthquake ground motion is investigated. In addition, sufficiency of using the first mode deformation, anticipated by the current design code, as the only possible deformation pattern for designing braced frames is studied. A set of twenty ground motions was applied to three 9-story buildings using two-story X-bracing and chevron bracing configurations. Two different braced-intersected girders were used in two-story X-braced frames to investigate the effect of beam strength on the frame response. Seismic responses of the frames were discussed in terms of seismic demand on the columns and braces. The study concludes that columns in two-story X-braced frames, designed based on current design code, experience yielding during an earthquake ground motion, and it is not safe to use the first mode deformation as the only possible deformation pattern for designing the braced frames. This study also finds that seismic demand on the braces in the two-story X-braced frames are quite significant and are prone to fracture.